Leadership Language: Articulating the Value of Nursing’s Contributions to Healthcare - Lynn D. Mohr; Cynthia Rothenberger; Lynn Marilyn Schallom; Susan C. Dresser; Jennifer K. Peterson; Cherrie L. Pullium; MaryBeth Modic; Tracy Campbell; Gail A. Bagwell; Jennie Matays (JONA: The Journal of Nursing Administration, 2026)
Passive language patterns undermine nursing’s professional influence by obscuring clinical expertise and the inherent value of nursing. This article offers a practical approach for transforming nursing practice language across clinical, educational, organizational, and systems leadership. Using 4 core principles: using active leadership verbs, connecting actions to outcomes, emphasizing expertise and evidence-based practice, and demonstrating influence through change-oriented language. This approach provides specific language transformations that demonstrate nursing’s strategic value, strengthen financial acumen, and drive policy change. It is important to note that this transformation emphasizes nursing’s core values and ensures nursing is recognized and resourced appropriately.